2005
DOI: 10.1099/mic.0.28437-0
|View full text |Cite
|
Sign up to set email alerts
|

bph genes of the thermophilic PCB degrader, Bacillus sp. JF8: characterization of the divergent ring-hydroxylating dioxygenase and hydrolase genes upstream of the Mn-dependent BphC

Abstract: Bacillus sp. JF8 is a thermophilic polychlorinated biphenyl (PCB) degrader, which utilizes biphenyl and naphthalene. A thermostable, Mn-dependent 2,3-dihydroxybiphenyl 1,2-dioxygenase, BphC_JF8, has been characterized previously. Upstream of bphC are five ORFs exhibiting low homology with, and a different gene order from, previously characterized bph genes. From the 59 to 39 direction the genes are: a putative regulatory gene (bphR), a hydrolase (bphD), the large and small subunits of a ring-hydroxylating diox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 76 publications
1
14
0
1
Order By: Relevance
“…Six gene pairs in region A, Mvan_0463/0464 (phtAaAb), 0487/0488 (nidAB), 0525/0526 (nidA3B3), 0533/0534, 0539/0540, and 0546/0547, have been previously identified to be involved in aromatic hydrocarbon degradation (Khan et al 2001;Stingley et al 2004;Kim et al 2006Kim et al , 2007Kweon et al 2007). Sequence analysis indicated that Mvan_0546/0547 also likely transforms other PAHs including phenanthrene, naphthalene, and biphenyl because it contains a considerable sequence similarity to other enzymes having such substrate specificities (Larkin et al 1999;Mukerjee-Dhar et al 2005). The seventh RHO pair in region A, Mvan_0492/0493 is similar to the salicylate hydroxylase from Sphingomonas sp.…”
Section: Genes Involved In the Upper Pathway Of Pah Degradationmentioning
confidence: 96%
“…Six gene pairs in region A, Mvan_0463/0464 (phtAaAb), 0487/0488 (nidAB), 0525/0526 (nidA3B3), 0533/0534, 0539/0540, and 0546/0547, have been previously identified to be involved in aromatic hydrocarbon degradation (Khan et al 2001;Stingley et al 2004;Kim et al 2006Kim et al , 2007Kweon et al 2007). Sequence analysis indicated that Mvan_0546/0547 also likely transforms other PAHs including phenanthrene, naphthalene, and biphenyl because it contains a considerable sequence similarity to other enzymes having such substrate specificities (Larkin et al 1999;Mukerjee-Dhar et al 2005). The seventh RHO pair in region A, Mvan_0492/0493 is similar to the salicylate hydroxylase from Sphingomonas sp.…”
Section: Genes Involved In the Upper Pathway Of Pah Degradationmentioning
confidence: 96%
“…Although the annotation of BphD JF8 from Bacillus sp. strain JF8 (25) suggests that this class III enzyme is involved in biphenyl catabolism, the ringhydroxylating dioxygenase encoded by the operon containing bphD JF8 is most closely related to enzymes that catalyze angular dioxygenation, strongly suggesting that the natural substrate of BphD JF8 is also an ortho-substituted HOPDA. The third putative MCP hydrolase of S. wittichii RW1 (2), encoded by orfG7, is evolutionarily divergent from other MCP hydrolases.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the Mn(II)-dependent BphC and BphD ( fig. 4 ) evidently belong to new subfamilies in the phylogeny of extradiol dioxygenases and hydrolases acting on extradiol cleavage products [Hatta et al, 2003;Mukerjee-Dhar et al, 2005].…”
Section: Metabolic Versatilitymentioning
confidence: 99%
“…The bph operon of Bacillus sp. JF8 harbors a novel bphRDA1A2BC cluster [Mukerjee-Dhar et al, 2005] ( fig. 3 ) encoding enzymes only distantly related to enzymes previously described to be important for biphenyl degradation ( fig.…”
Section: Metabolic Versatilitymentioning
confidence: 99%
See 1 more Smart Citation